Local electronic structure of the peptide bond probed by resonant inelastic soft X-ray scattering - Weinhardt, Lothar; Benkert, Andreas; Meyer, Frank; Zharnikov, Michael; Reinert, Friedrich; Heske, Clemens (Physical chemistry, chemical physics, 2019)
The local valence orbital structure of solid glycine, diglycine, and triglycine is studied using soft X-ray emission spectroscopy (XES), resonant inelastic soft X-ray scattering (RIXS) maps, and spectra calculations based on density-functional theory. Using a building block approach, the contributions of the different functional groups of the peptides are separated. Cuts through the RIXS maps furthermore allow monitoring selective excitations of the amino and peptide functional units, leading to a modification of the currently established assignment of spectral contributions. The results thus paint a new-and-improved picture of the peptide bond, enhance the understanding of larger molecules with peptide bonds, and simplify the investigation of such molecules in aqueous environment.
Published on May 31, 2019
Gesehen am 30.10.2019